Competency, Needs for Professional Progression Development, and Associated Factors among Public Health Professional Personnel in Thailand - Maneenin, Naowarat; Laohasiriwong, Wongsa; Bangchuad, Paisan; Sornlorm, Kittipong; Pongpanich, Sathirakorn; Boukam, Tasanee; Sudjit, Somjai; Paotui, Mana; Timtub, Anek; Charoenpon, Supot; Hnuploy, Kanit (Health Science Journal of Thailand, 2022)
This cross-sectional study aimed to describe the situation, distribution, job characteristics, competency, and development needs among public health professional personnel as well as its associated factors. The samples were 2,085 public health professional personnel who were multi-stage randomly selected to respond to a self-administered structured questionnaire. Data analysis was performed by using descriptive statistics and multiple logistic regression used to identify factors associated with the need for professional progression development among public health professional personnel. The results indicated that the highest proportion of competency they got from the studied program was health promotion and community health (49.16 percent). Most of the personnel needed further education (63.75%), which factors associated with the needs for professional progression development were; professional development was a condition for higher position promotion (AOR = 5.38, 95%CI: 4.06–7.13), professional development was a demand of the organization (AOR = 3.67, 95%CI:2.76–4.88), their own need for continuing study at a higher level (AOR = 3.00, 95%CI: 2.39–3.76), to develop competency (AOR = 2.71, 95%CI:2.15 – 3.42), organization supported for continuing study (AOR = 2.71, 95%CI: 2.12–3.47), a demand of father/mother or parents (AOR = 1.64, 95%CI: 1.21–2.22). Therefore, organizational policy and supports are essential for the professional progression development of public health professional personnel in Thailand.